2000
DOI: 10.1055/s-2000-8451
|View full text |Cite
|
Sign up to set email alerts
|

Body Weight Gain after Administration of Antipsychotic Drugs: Correlation with Leptin, Insulin and Reproductive hormones

Abstract: Excessive body weight gain, hyperprolactinemia and low gonadal steroid serum levels are often observed during chronic administration of antipsychotic drugs (AP). Clinical and experimental findings suggest that leptin, the peptidic hormone involved in long-term body weight regulation, and reproductive hormones are interrelated. Therefore, we assessed circulating leptin levels in healthy, lean women (n = 12) and men (n = 7) before and after short-term administration of the AP sulpiride (SUL, 200 mg/day). In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
11

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 34 publications
1
43
0
11
Order By: Relevance
“…34 A positive correlation between leptin and BMI was detected only in the female control group, a finding in agreement with previous reports. 35 Since the BMI of the patients is lower than that of the gender matched control group, it could be concluded that adipose tissue is unable to maintain adequate leptin production when a higher leptin secretion is required, suggesting that the inappropriately low leptin secretion or decreased leptin/ghrelin ratio could contribute to the relevant pathology, namely the irregular menses or amenorrhea of the thalassemic females. Obviously, more data are needed for a valid interpretation of our findings, which may have relevance to other forms of irregular menses or amenorrhea.…”
Section: Resultsmentioning
confidence: 99%
“…34 A positive correlation between leptin and BMI was detected only in the female control group, a finding in agreement with previous reports. 35 Since the BMI of the patients is lower than that of the gender matched control group, it could be concluded that adipose tissue is unable to maintain adequate leptin production when a higher leptin secretion is required, suggesting that the inappropriately low leptin secretion or decreased leptin/ghrelin ratio could contribute to the relevant pathology, namely the irregular menses or amenorrhea of the thalassemic females. Obviously, more data are needed for a valid interpretation of our findings, which may have relevance to other forms of irregular menses or amenorrhea.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, in many instances leptin levels increased significantly without significant changes in serum insulin, other glycemic or lipid measures (Zhang et al, 2004;Murashita et al, 2005;Sporn et al, 2005;Chiu et al, 2006;Hosojima et al, 2006;Atmaca et al, 2007). One cross-sectional study in bipolar subjects also found no correlation between any glucose or lipid parameter and leptin levels (Gergerlioglu et al, 2006), although a small number reported significant correlations between leptin and serum insulin (Baptista et al, 2000;Melkersson et al, 2000;Melkersson and Hulting, 2001), glucose (Wang et al, 2006) and serum triglycerides (Atmaca et al, 2003c); however, most of the authors reporting significant correlations did not control for BMI.…”
Section: Other Metabolic Parametersmentioning
confidence: 97%
“…Numerous subsequent prospective trials of olanzapine-treated patients (Eder et al, 2001;Graham et al, 2005b;Ebenbichler et al, 2005;Murashita et al, 2005;Hosojima et al, 2006) and clozapine-treated patients (Monteleone et al, 2002;Kivircik et al, 2003;Sporn et al, 2005;Theisen et al, 2005) confirmed the association between use of these medications, weight gain, and increased serum leptin levels. For agents with less weight gain liability, such as high potency typicals (Hagg et al, 2001;Atmaca et al, 2003a;Atmaca et al, 2003c), sulpiride (Baptista et al, 2000), quetiapine (Atmaca et al, 2003c), or risperidone (Fitzgerald et al, 2003;McIntyre et al, 2003;Martin et al, 2004;Chiu et al, 2006), comparative trials noted modest weight gain and leptin changes, while olanzapine and clozapine exposed subjects experienced marked increases in adiposity, weight and serum leptin. A few prospective trials which examined the effect of pharmacological weight-modifying strategies using adjunctive amantadine (Graham et al, 2005a) or nizatidine (Atmaca et al, 2003b;Atmaca et al, 2004) found positive effects of the adjunctive medication, with proportional differences in leptin levels compared to those treated with antipsychotic alone.…”
Section: Leptin Drug Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, drugs that block dopamine D2 receptors increase appetite and result in significant weight gain. Healthy subjects treated with antipsychotic drugs (dopamine antagonists) gain weight (3). Furthermore, of particular interest is the recent report that dopamine deficiency in obese individuals may perpetuate pathological eating and strategies aimed at improving dopamine function may be beneficial in the treatment of obese individuals (4).…”
Section: Introductionmentioning
confidence: 99%